Sustainable Development of Inclusive and Disability-Friendly Tourism in the Pasir Padi Beach Area, Bangka Belitung, Indonesia - Zakiyah, Ummi; Agus Sofyan; Suryani (Politeknik Pariwisata NHI Bandung, 2025)
Inclusive tourism emphasizes the principle of equal access to tourism facilities and infrastructure, ensuring that tourism benefits are accessible to all individuals, including persons with disabilities and marginalized communities, while simultaneously supporting environmental conservation and long-term sustainability. This study aims to explore the readiness of Pasir Padi Beach in implementing inclusive tourism by examining physical accessibility, such as adequate infrastructure, wheelchair-friendly pathways, and accessible transportation, as well as inclusive services, information availability, and social acceptance in developing a disability-friendly and sustainable tourism destination. This study adopts a qualitative research approach using a descriptive and exploratory design. Data were collected through in-depth interviews with key stakeholders, including local government officials, destination managers, tourism service providers, and community representatives. These data were complemented by direct field observations and document analysis related to tourism planning and accessibility policies. Qualitative data analysis was conducted using NVivo software to identify dominant themes, stakeholder perspectives, and institutional readiness related to inclusive tourism development. The findings indicate that Pasir Padi Beach has demonstrated initial commitment toward inclusive tourism; however, several gaps remain, particularly in standardized accessibility infrastructure, integrated planning, and public awareness regarding disability inclusion. The study further reveals that multi-stakeholder collaboration among government agencies, destination managers, local communities, and the private sector plays a decisive role in establishing an adaptive, inclusive, and equitable tourism system. Inclusive tourism development is found to contribute not only to social justice and equal participation but also to market diversification, destination competitiveness, and long-term sustainability. In conclusion, the development of inclusive tourism at Pasir Padi Beach requires a comprehensive, participatory, and sustainability-oriented approach. This study contributes to the growing body of inclusive tourism literature and supports the achievement of the Sustainable Development Goals (SDGs), particularly those related to equality, reduced inequalities, and sustainable cities and communities.